Figurative Language in Female Islamic Preaching: A Case Study of Ustadzah Mumpuni Handayekti - Wati, Dyah Rohma; Cahyono, Dwi; Hanik, Asmah (Universitas Pamulang, 2026)
A Preacher has duty to convey the preaching to congregation. In order to make the preaching understood and accepted, a preacher need strategy to convey the preaching, one of them is using figurative language. This study aims to examine figurative language in Islamic preaching of Ustazah Mumpuni Handayayekti (UMH), explain the purposes of figurative language used in the preaching, and show the dominant of figurative language used in UMH’s preaching. This study used a qualitative approach. The data in this study were resourced from utterances of Ustazah UMH in two preaching videos broadcast on the You tube channel. The data were collected by means of listening method. Its basic technique is tapping, while its advanced ones are free engagement speaking technique (SBLC) and note-taking technique and analyzed by using interactive model by Miles, Huberman, dan Saldana which includes data collection, data condensation, data display, and conclusion, drawing/ verification. The result show that in Ustazah MH’s preaching, there are six figurative languages used in MH’s preaching, they are synecdoche, simile, personification, metonymy, irony, and metaphor that the most dominant type of figurative language was simile with the percentage of 27%. The purposes of figurative language used in MH’s preaching are emphasizing a statement, expressing humor to freshen up the atmosphere, expressing praise, and expressing sarcasm with subtle language.